Closantel toxicity in a pregnant ewe at mid gestation: the pathological evaluation of the ewe and lamb nine months later. Issue 1 (27th August 2014) - Hannon, Fergus Patrick; Ellis, Kathryn Amanda; Guevar, Julien; Marchesi, Francesco; Geraghty, Timothy; Leach, Joshua David George
Abstract : In February 2013, a flock of 20 pastured ewes was treated with oral closantel. Within 10 days of dosing, one 2‐year‐old Texel‐cross ewe that was approximately three months in lamb was noticed to be spending a prolonged time in recumbency. On the 6th of March, the animal was referred to Scottish Centre for Production Animal Health and Food Safety (SCPAHFS). At admission, the ewe appeared blind, pupils were dilated with a negative menace response and pupillary light reflex bilaterally. Closantel toxicity was suspected. Following admission, this ewe was housed and was stable despite remaining blind. On April 21, a single male lamb was born. This lamb was found to have normal clinical and neurological parameters over five months of observation following birth. On postmortem examination closantel toxicity was confirmed in the ewe while following detailed gross and histological examination of all tissues of the lamb there was no indication of the toxicity suffered by its mother.